Stimulative Effects of Hominis Placental Pharmacopuncture Solution Combined with Zinc-oxide Nanoparticles on RAW 264.7 Cells - Hong Tae-Keun; Kim Jeehye; Woo Juyoun; Ha Ki-Tae; Joo Myungsoo; Hahn Yoon-Bong; Jeong Han-Sol (Korean Pharmacopuncture Institute, 2012)
Objectives: The purpose of this study is to examine whether Hominis Placental pharmacopuncture solution (HPPS) combined with zinc-oxide nanoparticles (ZnO NP) activates RAW 264.7 cells. Methods: We soaked ZnO nanoparticles in the Hominis Placenta pharmacopuncture solution, thereby making a combined form (ZnO NP HPPS). The effect of ZnO NP HPPS on the intracellular reactive oxygen species (ROS) production was measured by 2', 7'-dichlorofluorescin diacetate (DCFH-DA) assay. The effect of ZnO NP HPPS on NF-κ B was measured by using a luciferase assay. The effect of ZnO NP HPPS on the cytokine expression was assessed by semi-quantitative reverse transcriptase polymerase chain reaction (RT-PCR). The cellular uptake of ZnO NP HPPS was measured by using a flow cytometric analysis, and cellular structural alterations were analyzed by using transmission electron microscopy (TEM). Results: Neither the HPPS nor the ZnO NPs induced intracellular ROS production in RAW 264.7 cells. Neither of the materials activated NF-κ B or it's dependent genes, such as TNF-α, IL-1, and MCP-1. However, ZnO NP HPPS, the combined form of ZnO NPs and HPPS, did induce the intracellular ROS production, as well as prominently activating NF-κ B and it's dependent genes. Also, compared to ZnO NPs, it effectively increa-sed the uptake by RAW 264.7 cells. In addition, cellular structural alterations were observed in groups treated with ZnO NP HPPS. Conclusions: Neither ZnO NP nor HPPS activated RAW 264.7 cells, which is likely due to a low cellular uptake. The ZnO NP HPPS, however, significantly activated NF-κ B and up-regulated its dependent genes such as TNF-α, IL-1, and MCP-1. ZnO NP HPPS was also more easily taken into the RAW 264.7 cells than either ZnO NP or HPPS.